Characterising the tidal stream power resource around France using a high-resolution harmonic database. (August 2018) - Guillou, Nicolas; Neill, Simon P.; Robins, Peter E.
Abstract: Although tidal stream energy is highly predictable, the distribution of the resource varies over small spatial scales and over tidal-to-decadal time scales, requiring detailed models and accurate analysis techniques. The present study investigates the spatial and temporal variability of the tidal stream energy resource around France, using a tidal current harmonic database. The 250 m resolution tidal database covers western Brittany and the western English Channel, two regions that have strong potential for tidal array development. As well as generating a refined resource assessment for the region, a series of metrics are considered to assess resource variability, both spatially and temporally. Particular attention is dedicated to variability over spring-neap time scales (resulting from M 2 and S 2 compound tides) and current asymmetry (governed by M 2 and M 4 velocities). A clear contrast in the nature of the resource is found between sites located off the Cotentin Peninsula, which exhibit low spring-neap variability and tidal asymmetry, leading to a more continuous and therefore attractive energy conversion, and sites in western Brittany, with greater variabilities over semi-diurnal and fortnightly time scales. Highlights: The spatio-temporal variability of tidal stream power resource around France is investigated. A 250 m tidal current harmonic database is exploited with specific technical methods. Particular attention is made to spring-neap tidal variability and semi-diurnal asymmetry. Such variabilities reduce power consistency over daily-to-fortnightly time scales. A contrast is exhibited between sites off the Cotentin Peninsula and in western Brittany.